2021
DOI: 10.1186/s12883-021-02312-7
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions associated with subarachnoid hemorrhage: a multicenter case-crossover study

Abstract: Background Most spontaneous subarachnoid hemorrhages (SAH) occur unexpectedly and independently of classical risk factors. In the light of increasing climate variability and change, we investigated weather and rapid weather changes as possible short-term risk factors for SAH. Methods Seven hundred ninety one patients admitted to three major hospitals in Germany for non-traumatic SAH with a determinable onset of SAH symptoms were included in this ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Increased SAH risk has been reported in correlation with increasing atmospheric pressure in different geographical regions [34][35][36][37][38][39][40] , while other studies report on an increased SAH risk associated with decreased atmospheric pressure 41 or even absence of association 25,27 . There is a significant number of published papers showing some kind of association between atmospheric pressure change and SAH incidence, probably because papers with negative results are rarely published, as pointed previously 31 . Furthermore, several authors speculate that atmospheric pressure may affect blood or intracranial pressure, leading to possible IA rupture 40,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased SAH risk has been reported in correlation with increasing atmospheric pressure in different geographical regions [34][35][36][37][38][39][40] , while other studies report on an increased SAH risk associated with decreased atmospheric pressure 41 or even absence of association 25,27 . There is a significant number of published papers showing some kind of association between atmospheric pressure change and SAH incidence, probably because papers with negative results are rarely published, as pointed previously 31 . Furthermore, several authors speculate that atmospheric pressure may affect blood or intracranial pressure, leading to possible IA rupture 40,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was previously suggested and discussed that an additional possible risk factor of IA rupture and SAH could be seasonal or meteorological factors; some studies found that meteorological changes were associated with an increased incidence of SAH [18][19][20][21][22][23][24][25][26] , whereas others report absence of such association [27][28][29][30][31] . When observing and analyzing the data presented, the associations that have been observed appear to be conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…A study found that the incidence of subarachnoid hemorrhage was higher during the months characterized by higher temperatures and higher relative humidity. Specifically, the study reported that the risk of subarachnoid hemorrhage was higher by 39% in males on days with an increase in relative humidity by 17.6% [11]. It is possible that high humidity may increase blood pressure and promote the development of cerebral aneurysms, which could contribute to the increased risk of subarachnoid hemorrhage.…”
Section: Humiditymentioning
confidence: 98%
“…M. Kockler и соавт. выявили слабую статистическую связь между повышением атмосферного давления и повышением частоты аневризматического САК через 3 дня [13].…”
Section: аневризматическое субарахноидальное кровоизлияние и метеорол...unclassified
“…в пятилетнем ретроспективном анализе не обнаружили влияния изменений температуры воздуха и колебаний атмосферного давления на частоту аневризматического САК, при этом выявили, что высокая влажность являлась статистически значимым фактором риска. Однако в ряде других исследований влияние влажности воздуха на риск разрыва ЦА не подтвердилось [3,4,6,13].…”
Section: научный обзор факторы риска аневризматического субарахноидал...unclassified